(untitled) (Journal of Plant Disease Sciences, 2023)
In the present investigation, Trichoderma harzianum, T. koningii, T. longibrachiatum, Bacillus subtilis and three strains of Pseudomonas fluorescens were tested in vitro for their efficacy against the chrysanthemum leaf blight causing Alternaria alternata. A screening study was also conducted to identify resistant chrysanthemum sources against the leaf blight disease caused by A. alternata. Amongst the bio-agents investigated, Trichoderma koningii, T. harzianum and T. longibrachiatum completely inhibited the mycelium of A. alternata. P. fluorescens strain- 2 (45.33) and Bacillus subtilis (43.71%) showed the least inhibition. Only one (cv. Red Star) of the ten chrysanthemum varieties tested in vivo for resistance to Alternaria alternata (Red Star) demonstrated a resistant reaction with a disease incidence of 4.90%. Yellow, Multiflora, and Manga red were moderately resistant, with disease incidence ranging from 17.03 to 19.20%. Oliveria white and Charlie were very susceptible to the disease, with disease incidence rates of 55.20 and 76.70 percent, respectively.